PENYELESAIAN MASALAH TUMPANG TINDIH (OVERLAPPING) PERIJINAN PERTAMBANGAN DAN HAK GUNA USAHA PT. MAHAKAM SUMBER JAYA DENGAN MASYARAKAT DI TENGGARONG SEBERANG - Fitriana Gamas (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Purpose Presidential Decree No. 1 of 2000 on the Implementation Task Synchronization Keagrariaan the field of Mining, Transmigration and Public Works, may not run as expected because of the ego of each sectoral institution. Although Presidential Decree referred to this day has never been repealed, but the cultural force among sectors that occur in the field still seems to be happening, even at the level of the wisdom.The method used in this study is the Legal Writing Empirical Legal Studies is a research field of data Primary and Secondary Data, Primary data was obtained through the interview process to the parties concerned, while the data over to the Secondary binding legal entity that is related Act the problems that occur.Based on the real conditions that exist that factor Overlapping Problems Cause Occurrence (overlapping) Permitting Mining and leasehold PT. Mahakam Sumber Jaya with the people in the village of Bukit Pariaman Management is influenced by factors lack of Human Resources (HR), nepotism, sectoral ego, and ignore the provisions, as well as land clearing has been no permission, technical considerations, there is involvement of some related agencies, weak supervision and control of the implementation of the District forest Service and forest protection activities in the District Tenggarong Seberang.Efforts in the travel between government agencies to solve the overlapping problem is that the government will only be passive and wait for the report from the parties, the parties requested clarification related Mining overlapping permission granted by the local government. In fact there has been a letter from the Ministry of Forestry, No. 327/Menhut-VII/2013, which occurs when the core issue is the responsibility of the holder IPPKH (PT.Mahakam source jaya) is coordinated with the local government.Based on the results of research at PT. Mahakam Sumber Jaya that improve the livelihoods of the community, other than that of the overlapping that occurs between mining companies with plantation companies are also being taken care of by the company and the relevant agencies in point is the Regional Agency for the Environment of Life (BLHD) sebaga Mediator Mediation process that has been implemented.